2006
DOI: 10.1002/hep.21214
|View full text |Cite
|
Sign up to set email alerts
|

Interindividual variability of canalicular ATP-binding-cassette (ABC)–transporter expression in human liver

Abstract: Interindividual variability in hepatic canalicular transporter expression might predispose to the development of hepatic disorders such as acquired forms of intrahepatic cholestasis. We therefore investigated expression patterns of bile salt export pump (BSEP, ABCB11), multidrug resistance protein 3 (MDR3, ABCB4 ), multidrug resistance associated protein 2 (MRP2, ABCC2 ) and multidrug resistance protein 1 (MDR1, ABCB1) in healthy liver tissue of a white population. Protein expression levels were correlated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
171
1
2

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 209 publications
(184 citation statements)
references
References 39 publications
(44 reference statements)
10
171
1
2
Order By: Relevance
“…Therefore, individuals with the 1331CC genotype had an ABCB11 expression of 80% compared with those harboring the 1331TT genotype. Our in vitro study reinforced the results of Byrne et al (2009) and Meier et al (2006) and identified decreased protein stability as a cause of reduced protein expression. Although some missense mutations, such as the D482G, enhanced aberrant splicing shown using a minigene system, this SNP (1331T.C) did not alter the pre-mRNA splicing pattern (Byrne et al, 2009).…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Therefore, individuals with the 1331CC genotype had an ABCB11 expression of 80% compared with those harboring the 1331TT genotype. Our in vitro study reinforced the results of Byrne et al (2009) and Meier et al (2006) and identified decreased protein stability as a cause of reduced protein expression. Although some missense mutations, such as the D482G, enhanced aberrant splicing shown using a minigene system, this SNP (1331T.C) did not alter the pre-mRNA splicing pattern (Byrne et al, 2009).…”
Section: Discussionsupporting
confidence: 87%
“…In contrast, 444V was expressed to a greater extent than 444A in CHO-K1 cells (Byrne et al, 2009). Meier et al (2006) studied the hepatic expression of ABCB11 protein in 110 individuals undergoing liver resection and demonstrated a trend toward reduced expression in individuals harboring the 1331C-allele (444A) polymorphism compared with those harboring the 1331T-allele (444V). Semiquantitative evaluation revealed a 1.15-fold higher hepatic ABCB11 protein expression level in individuals with the 1331CC genotype and 0.9-fold lower level in those with the 1331TT genotype when compared with those with the 1331TC genotype.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A strong candidate is the genetic background. Recently, the variation of BSEP protein expression levels was studied in 110 healthy liver specimens by Western blotting [63]. BSEP expression levels of these individuals were found to display a unimodal distribution and showed no correlation with, for example, sex or medication.…”
Section: Geneticsmentioning
confidence: 99%
“…12 Rare ABCC2 variants such as 1446C4G, 3563T4A and 4544G4A were described to be associated with higher mRNA and protein expression in liver, respectively. 13,14 Currently, it is not exactly known how and on which stage genetic variants interfere with the gene expression of ABCC2. Considering the full-length cDNA of ABCC2, we conducted different in vitro approaches to systematically follow the molecular effect of the most common SNPs (À24C4T, 1249G4A and 3972C4T) in Caucasians.…”
Section: Introductionmentioning
confidence: 99%